Recording reality, desiring the real - Cowie, Elizabeth (Visible evidence, 2011)
Documentary has once again emerged as one of the most vital cultural forms, whether seen in cinemas or inside the home, as digital, film, or video. This book looks at the history of documentary and its contemporary forms, showing how it has been simultaneously understood as factual, as story, as art, and as political, addressing the seeming paradox between the pleasures of spectacle in the documentary and its project of informing and educating.